Improving the Energy Efficiency of the Use of Oil Jet Pumps - D. A. Panevnyk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The substantiation of the choice of design parameters characterizing the mutual orientation of the mixed flows and the ratio of the geometric dimensions of the elements of the flow path of the jet pump that provide an increase in the energy characteristics of borehole ejection systems is given. Depending on the mutual orientation of the mixed flows, three variants of the design of the jet pump are possible, viz. the one with a parallel orientation of the working and ejected flows, the one with the inlet of the ejected flow at a sharp angle, and the one with a perpendicular orientation of the working and ejected flows. The magnitude of the angle between the velocity vectors of the mixed flows directly affects the intensity of vortex formation in the mixing chamber, the amount of energy loss and the efficiency of the jet pump; however, the simplicity of their manufacture remains the determining condition for choosing the design variant of the elements of ejection systems. Based on the use of the laws of conservation of energy, the amount of motion and continuity of the flow, it is determined that the level of energy loss during mixing flows is directly proportional to the magnitude of the angle of entry of the ejected medium. In the course of computer simulation of the jet pump workflow, an asymmetric distribution of hydrodynamic parameters for the non-parallel orientation of the mixed flows has been obtained. In order to reduce energy losses when mixing flows, the value of the angle of entry of the ejected flow must be taken in the range from 0 to 15°. In the case of the implementation of the zero head mode and the maximum ejection coefficient, minimal energy losses during mixing of flows are provided for the main geometric parameter of the jet pump equal to 2.375. In the course of experimental studies, the inverse dependence of the maximum value of the efficiency of a borehole jet pump on the value of its main geometric parameter represented as a power function, has been established. When using ejection systems that implement long-term technological processes (e. g., during oil production), it is necessary to take the minimum possible value of the main geometric parameter of the jet pump for the specified operating conditions.